Penerapan Konsep Paradise of Bali terhadap Healthy Refleksiologi and Fitness Center - Setiono, Vincentius Laurent (Intra, 2013)
Interior Designing Healthy Reflexology and Fitness Center was made due with a growing era, more and more people are not concerned with health, while the burden of work they have to do that will ease the increasing occurrence of stress that makes the muscles become tense, nervous impaired, body poisons buried, substandard blood circulation resulting in reduced arousal works. Therefore health is a very important thing for the community.In order for the data collection to be valid then designed several methods of design methodologies such as observation (direct observation), interviews with the instructor, the library to get the theories that support the validity of field data, and documentation to supplement the data obtained.Through the concept of Paradise of Bali which is applied every related kinds of interior elements and furniture, people can find a comfortable and attractive place to do sports, and increase the motivation of the health visitor. In this design also provides adequate facilities to meet the needs of the community fitness facility.